PERBANDINGAN BIAYA PEMBANGUNAN RUMAH SEDERHANA DENGAN RUMAH KONSEP AMAN GEMPA BERDASARKAN ANALISA BENEFIT COST RATIO SKENARIO GEMPA 50 TAHUN - Natalia, Monika; Mirani, Zulfira; Mafriyal, Mafriyal; Sari, Desnila; Hanum, Riska Fauziah (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2024)
In mitigation to minimize the risk of earthquakes, protection is needed to reduce the impacts. Damage caused by earthquakes can be minimized by planning and building earthquake-resistant houses. To get an earthquake-resistant house, by adding earthquake-strengthening components based “Pedoman Teknis Rumah dan Bangunan Gedung Tahan Gempa and SNI 1726-2019”. This research aims to design earthquake-resistant houses concept for an earthquake period of 50 years and analyze the benefit-cost ratio by comparing residential houses designed with earthquake-safe features to conventional residential houses. The concept of earthquake-resistant houses is carried out in conventional type 120 residential houses. The research results that the cost for a conventional residence is IDR 387,223,000 and the cost of an earthquake house concept is IDR. 407,593,000, where there is a cost difference of IDR 20,370,000 or 5% (more expensive). Benefit-cost ratio value for conventional residential houses for the 50-year earthquake scenario is 0.64; 0.71; 0.77; 0.82; and 0.87 where the value of BCR <1, then this residential house is not effective in facing a 50-year earthquake scenario. Benefit-cost ratio for earthquake-safe housing was 1.12; 1.34; 1.58; 1.84; and 2.09. The BCR>1 and the value moves up until the 50th year. So with an additional cost of 5% for earthquake-safe features, this house is considered very effective for the 50-year earthquake period scenario.